Comparative Transcriptomics Uncover the Uniqueness of Oocyte Development in the Donkey - Zhang, Fa-Li; Zhang, Shu-Er; Sun, Yu-Jiang; Wang, Jun-Jie; Shen, Wei (Frontiers in Genetics, 2022)
The donkey is an important domestic animal, however the number of donkeys world-wide is currently declining. It is therefore important to protect their genetic resources and to elaborate the regulatory mechanisms of donkey reproduction, particularly, oocyte development. Here, we adopted comparative transcriptomic analysis and weighted gene co-expression network analysis (WGCNA) to uncover the uniqueness of donkey oocyte development compared to cattle, sheep, pigs, and mice, during the period from germinal vesicle (GV) to metaphase II (MII). Significantly, we selected 36 hub genes related to donkey oocyte development, including wee1-like protein kinase 2 (WEE2). Gene Ontology (GO) analysis suggested that these genes are involved in the negative regulation of cell development. Interestingly, we found that donkey specific differentially expressed genes (DEGs) were involved in RNA metabolism and apoptosis. Moreover, the results of WGCNA showed species-specific gene expression patterns. We conclude that, compared to other species, donkey oocytes express a large number of genes related to RNA metabolism to maintain normal oocyte development during the period from GV to MII.